Professional learning networks: a descriptive phenomenological study with primary school teachers in Greece - Ourania Maria Ventista; Stavroula Kaldi; Magdalini Kolokitha; Christos Govaris; Chris Brown (Quality Education for All)
Purpose – Professional learning networks (PLNs) involve teachers’ collaboration with others outside of their school to improve teaching and learning. PLNs can facilitate teachers’ professional growth and school improvement. This study aims to explore the drivers for participation within PLNs, the enactment process and the impact of PLN participation on teachers, students and schools in Greece. Design/methodology/approach – A descriptive phenomenological study was conducted to explore the lived experience of primary school teachers participating in PLNs. Findings – The findings showed that individuals who were open to change were driving innovation to address a need or a lack in their daily practice that was not satisfied within their usual community of practice. The key element of the participation was peer collaboration with openness of communication without attendant accountability pressures. The change was mainly identified in teacher skills and the school climate. An individual could bring change only if the school is already open to change. In some cases, resistance to change in schools was identified before enactment or during enactment. The transformation of teachers’ and leaders’ stances is discussed, enabling the opportunity to maximise school improvement. Originality/value – The study examines PLNs as European Union-funded initiatives that are developed by teachers in centralised education systems under the phenomenological research paradigm. It explores the PLNs in a different setting compared to the existing conceptual theory of change for PLNs.